1996
DOI: 10.3109/01612849609006532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Staff Use of Crisis Prevention Intervention Techniques: A Pilot Study

Abstract: The purpose of this pilot study was to evaluate staff use of crisis prevention intervention (CPI) techniques in averting crisis episodes at the various levels (anxiety, defensive, and acting out) of a crisis (resulting in reduction of seclusion and restraint episodes and patient/staff injuries). A descriptive correlational research design was used. Data were collected by nurse observers trained in CPI techniques through observation of patient incidents and staff interventions. A 51-item CPI instrument based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…In general, these elements are considered to be important for the success of any aggression management program (Farrell & Cubit, 2005). Another study found that 84.2% of incidents were resolved without the use of seclusion or restraint following staff training; however, this finding is from a methodologically weak study with no preintervention measurement (Jambunathan & Bellaire, 1996). …”
Section: Resultsmentioning
confidence: 99%
“…In general, these elements are considered to be important for the success of any aggression management program (Farrell & Cubit, 2005). Another study found that 84.2% of incidents were resolved without the use of seclusion or restraint following staff training; however, this finding is from a methodologically weak study with no preintervention measurement (Jambunathan & Bellaire, 1996). …”
Section: Resultsmentioning
confidence: 99%
“…Jambunathan & Bellaire (1996) did explore whether training improved staff's ability to handle violent situations. These researchers observed an adult unit's environment and patient management episodes to determine how staff utilized the crisis intervention techniques they had been taught.…”
Section: Restraint Reduction Though Skills Developmentmentioning
confidence: 99%
“…A unit embarking on a restraint-reduction program via crisis intervention training might use an evaluation method designed by Jambunathan and Bellaire (1996). Following unit-wide crisis intervention training, Jambunathan and Bellaire observed the unit milieu and patient management episodes to determine how staff utilized the crisis intervention techniques.…”
Section: Building Basic Staff Skillsmentioning
confidence: 99%